Profile of renal trauma victims treated at a university hospital in Curitiba - CESAR AUGUSTO BROSKA JÚNIOR; ANDRÉ DE CASTRO LINHARES; ANDRÉ MONTES LUZ; CARLOS ROBERTO NAUFEL JÚNIOR; MARIANA SANTOS DE-OLIVEIRA; ANDRÉ LUIZ BENÇÃO; GABRIELA VERONESE (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Objective: to study the profile of victims of kidney trauma who underwent surgical and medical treatment in a hospital in Curitiba. Methods: we conducted a retrospective, analytical, quantitative, cross-sectional study of patients with renal trauma admitted to the Evangelical Hospital of Curitiba between February 2011 and January 2014. Results: participated in the study 38 patients, four women and 34, men with a mean age of 28.4 years. Most injuries (60.5%) was due to closed mechanisms, especially motorcycle accidents. Injuries were treated conservatively in most cases. Patients who required surgical treatment had severe kidney damage or some other associated lesion, usually intra-abdominal. Hospital stay was lower in the conservative treatment group (10.8 days) compared with the surgical treatment one (18.8 days); mortality was also lower in the conservative treatment group (8.3%) compared with the surgical (14.3%). There were no deaths associated to kidney damage itself. Conclusion: patients with renal trauma in this study were young men, victims of motorcycle accidents, taking place during the night and early morning. Most injuries were treated conservatively.